Adapting the EU Economic Governance to New Macroeconomic and Political Realities - Raffaele Fargnoli (Intereconomics)
Abstract There was a widespread consensus on the need to modify fiscal rules in the EU even before the COVID-19 crisis. The aim of this article is to reflect on the reform of fiscal rules from a broader perspective, looking at three different dimensions: the political economy of fiscal rules in the current political and economic environment, the renewed debate about fiscal policy roles and objectives, as well as the current incomplete nature of the European Monetary Union and the prospects for its completion. The main contribution of this paper is to analyse EMU fiscal policy and the related governance modes from a broader perspective. Furthermore, the article briefly discusses ideas for a new model of fiscal and economc surveillance based on a cooperative governance system in order to better fit with with current macroeconomic and political realities.